Reduced rDNA transcription diminishes skeletal muscle ribosomal capacity and protein synthesis in cancer cachexia - Kim, Hyo-Gun; Huot, Joshua R; Pin, Fabrizio; Guo, Bin; Bonetto, Andrea; Nader, Gustavo A (The FASEB journal, 2021)
Muscle wasting in cancer is associated with deficits in protein synthesis, yet, the mechanisms underlying this anabolic impairment remain poorly understood. The capacity for protein synthesis is mainly determined by the abundance of muscle ribosomes, which is in turn regulated by transcription of the ribosomal (r)RNA genes (rDNA). In this study, we investigated whether muscle loss in a preclinical model of ovarian cancer is associated with a reduction in ribosomal capacity and was a consequence of impaired rDNA transcription. Tumor bearing resulted in a significant loss in gastrocnemius muscle weight and protein synthesis capacity, and was consistent with a significant reduction in rDNA transcription and ribosomal capacity. Despite the induction of the ribophagy receptor NUFIP1 mRNA and the loss of NUFIP1 protein, in vitro studies revealed that while inhibition of autophagy rescued NUFIP1, it did not prevent the loss of rRNA. Electrophoretic analysis of rRNA fragmentation from both in vivo and in vitro models showed no evidence of endonucleolytic cleavage, suggesting that rRNA degradation may not play a major role in modulating muscle ribosome abundance. Our results indicate that in this model of ovarian cancer-induced cachexia, the ability of skeletal muscle to synthesize protein is compromised by a reduction in rDNA transcription and consequently a lower ribosomal capacity. Thus, impaired ribosomal production appears to play a key role in the anabolic deficits associated with muscle wasting in cancer cachexia.